Particle platforms for cancer immunotherapy - Serda RE (Dove Medical Press, 2013)
Rita Elena Serda Department of Nanomedicine, The Methodist Hospital Research Institute, Houston, TX, USA Abstract: Elevated understanding and respect for the relevance of the immune system in cancer development and therapy has led to increased development of immunotherapeutic regimens that target existing cancer cells and provide long-term immune surveillance and protection from cancer recurrence. This review discusses using particles as immune adjuvants to create vaccines and to augment the anticancer effects of conventional chemotherapeutics. Several particle prototypes are presented, including liposomes, polymer nanoparticles, and porous silicon microparticles, the latter existing as either single- or multiparticle platforms. The benefits of using particles include immune-cell targeting, codelivery of antigens and immunomodulatory agents, and sustained release of the therapeutic payload. Nanotherapeutic-based activation of the immune system is dependent on both intrinsic particle characteristics and on the immunomodulatory cargo, which may include danger signals known as pathogen-associated molecular patterns and cytokines for effector-cell activation. Keywords: adjuvant, particle, immunotherapy, dendritic cell, cancer, vaccine